Acute toxicity and genotoxicity of silver nanoparticle in rats - Wen, Hairuo; Dan, Mo; Yang, Ying; Lyu, Jianjun; Shao, Anliang; Cheng, Xiang; Chen, Liang; Xu, Liming (PloS one, 2017)
The potential risk of a nanoparticle as a medical application has raised wide concerns, and this study aims to investigate silver nanoparticle (AgNP)-induced acute toxicities, genotoxicities, target organs and the underlying mechanisms. Sprague-Dawley rats were randomly divided into 4 groups (n = 4 each group), and AgNP (containing Ag nanoparticles and released Ag+, 5 mg/kg), Ag+ (released from the same dose of AgNP, 0.0003 mg/kg), 5% sucrose solution (vechicle control) and cyclophophamide (positive control, 40 mg/kg) were administrated intravenously for 24 h respectively. Clinical signs and body weight of rats were recorded, and the tissues were subsequently collected for biochemical examination, Ag+ distribution detection, histopathological examination and genotoxicity assays. The rank of Ag detected in organs from highest to lowest is lung>spleen>liver>kidney>thymus>heart. Administration of AgNP induced a marked increase of ALT, BUN, TBil and Cre. Histopathological examination results showed that AgNP induced more extensive organ damages in liver, kidneys, thymus, and spleen. Bone marrow micronucleus assay found no statistical significance among groups (p > 0.05), but the number of aberration cells and multiple aberration cells were predominately increased from rats dosed with Ag+ and AgNP (p < 0.01), and more polyploidy cells were generated in the AgNP group (4.3%) compared with control. Our results indicated that the AgNP accumulated in the immune system organs, and mild irritation was observed in the thymus and spleen of animals treated with AgNP, but not with Ag+. The liver and kidneys could be the most affected organs by an acute i.v. dose of AgNP, and significantly increased chromosome breakage and polyploidy cell rates also implied the potential genotoxicity of AgNP. However, particle-specific toxicities and potential carcinogenic effect remain to be further confirmed in a chronic toxicity study.